Civil commitment experiences among opioid users. (1st December 2018) - Christopher, Paul P.; Anderson, Bradley; Stein, Michael D.
Highlights: Committed opioid users have more drug use, overdoses and criminal justice problems. Post-commitment abstinence is associated with perceived judicial fairness. A third of committed opioid users relapsed on the day their release. Medication treatment for opioid use correlates with post-commitment abstinence. Abstract: Introduction: Civil commitment is an increasingly used policy intervention to combat the opioid epidemic. Yet little is known about persons who get committed and outcomes following commitment for opioid use. In the current cross-sectional study, we compared the characteristics of persons with and without a history of civil commitment, and the correlates of post-commitment abstinence. Methods: Between October 2017 and May 2018, we surveyed consecutive persons entering a brief, inpatient opioid detoxification (n = 292) regarding their lifetime experiences with civil commitment for opioid use. Results: Participants averaged 34.6 years of age, 27.1% were female, and 78.1% were White. Seventy-eight (26.7%) experienced civil commitment for opioid use at least once in their lifetime. Committed individuals had significantly higher rates of fentanyl, heroin, and injection drug use, drug overdoses, past incarceration, current criminal justice involvement, and past medication treatment for opioid use (p < .05). The average time to relapse following commitment was 72 days, although 33.8% relapsed on the same day of their release. Longer post-commitment abstinence was significantly associated with post-commitment medication treatment, higher perceived procedural justice (i.e., fairness) during the commitment hearing, positive attitude and higher motivation at the end of commitment, and improvement in attitude during commitment (p < .05). Conclusion: Opioid users who experience civil commitment constitute an especially high risk group. A positive commitment experience and post-commitment medication treatment are associated with longer post-commitment abstinence.